Assessment of injector-flow characteristics of additised and renewable diesel blends through high-speed imaging - Baran, Onur; Karathanassis, Ioannis K.; Koukouvinis, Foivos (Phoevos); Hwang, Joonsik; Pickett, Lyle M.; Spivey, David; Gavaises, Manolis (My University, 2023)
The influence of additives inducing viscoelasticity in diesel fuel, on the in-nozzle cavitation evolution and the expelled spray morphology has been quantified by high-speed, diffused back-light and schlieren imaging applied to two single-hole true-scale transparent injectors of straight and tapered orifice layouts (so-called Spray C and D of the engine Combustion Network), as well as a five-hole configuration (Spray M). More specifically, the in-nozzle cavitating flow and its effect on near-nozzle spray formation of a non-Newtonian diesel fuel sample treated with Quaternary Ammonium Salt (QAS) additives and exhibiting viscoelastic effects, as well as biodiesel (FAME), are compared against conventional diesel fuel for the first time. The operating conditions corresponded to injection and ambient pressures in the range of 500–900 bar and 1–20 bar, respectively. It was found that viscoelasticity has an overall suppressing effect on wall-attached, or so-called geometrical, cavitation. Furthermore, the investigation revealed that the action of viscoelastic additives has the capability to enhance the magnitude of well-established longitudinal vortices, with the subsequent after-effect of leading to increased cone angles of the expelled spray. On the contrary, it tends to suppress turbulence-induced transient instabilities in a manner similar to turbulence suppression.
Keywords: Cavitation; Diesel engines; Fuel additives; Non Newtonian flow; Spray nozzles; Turbulence; Viscoelasticity; Vortex flow